Evaluation of Yellow Fever Virus Infection in Aedes aegypti Mosquitoes from Pakistan with Distinct Knockdown Resistance Genotypes - Carlucio Rocha dos Santos; Caleb Guedes Miranda dos Santos; Dinair Couto-Lima; Bárbara Silva Souza; Rafi Ur Rahman; Marcos Dornelas Ribeiro; José Bento Pereira Lima; Ademir Jesus Martins (Insects)
Background: Yellow fever (YF) is an acute hemorrhagic disease endemic to Africa and Latin America; however, no cases have been reported in Asian regions with high Aedes aegypti infestation. Factors such as environmental conditions and genetic variations in the yellow fever virus (YFV) strains and mosquito populations may explain this absence. Mosquito populations have undergone strong selective pressure owing to the excessive use of insecticides. This pressure has led to the spread of alterations, such as knockdown-resistant mutations (kdr), which, while conferring resistance to pyrethroids, also induce various physiological side effects in the insect. Therefore, it is important to investigate whether the presence of kdr mutations influences the infectivity of YFV mosquitoes. This study evaluated the susceptibility of Ae. aegypti from Pakistan with distinct kdr genotypes to different YFV strains under laboratory conditions. Methods: Ae. aegypti from a Pakistani colony were exposed to YFV strains (PR4408/2008 and ES504/2017) along with the Rockefeller strain. After 14 days, RNA and DNA were extracted for viral RNA detection (qPCR) and kdr genotyping (TaqMan qPCR and HRM for T1520I and F1534C SNPs). Results: Pakistani Ae. aegypti were orally susceptible to YFV, with infection rates of 83.7% (PR4408/2008) and 61.3% (ES504), respectively, similar to Rockefeller. Two kdr genotypes (II + CC and TI + FC) were identified, with no significant differences in viral infection or dissemination rates. Conclusions: The Ae. aegypti population from Asia is capable of YFV infection and dissemination, regardless of kdr genotype.